2002
DOI: 10.1002/neu.10146
|View full text |Cite
|
Sign up to set email alerts
|

Unconventional ligands and modulators of nicotinic receptors

Abstract: ABSTRACT:Evidence gathered from epidemiologic and behavioral studies have indicated that neuronal nicotinic receptors (nAChRs) are intimately involved in the pathogenesis of a number of neurologic disorders, including Alzheimer's disease, Parkinson's disease, and schizophrenia. In the mammalian brain, neuronal nAChRs, in addition to mediating fast synaptic transmission, modulate fast synaptic transmission mediated by the major excitatory and inhibitory neurotransmitters glutamate and GABA, respectively. Of maj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
151
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 190 publications
(152 citation statements)
references
References 174 publications
(205 reference statements)
1
151
0
Order By: Relevance
“…Although endogenous KYNA can also activate the G-protein-coupled receptor GPR35 (Cosi et al, 2010;Wang et al, 2006), inhibition of a7nAChRs and, possibly, NMDARs appears to be the primary physiological function of extracellular KYNA in the mammalian brain (see below). As both a7nAChRs and NMDARs are critically involved in many important physiological functions, including cognitive processes (Bannerman et al, 2006;Levin et al, 2006;Robbins and Murphy, 2006;Thomsen et al, 2010), and also have a role in the etiology of neurodegenerative and other catastrophic brain diseases (Kalia et al, 2008;Kantrowitz and Javitt, 2010;Martin and Freedman, 2007;Mudo et al, 2007), detection of KYNA in the mammalian brain (Moroni et al, 1988;Turski et al, 1988) immediately suggested an important role of the metabolite in both physiology and pathology (Pereira et al, 2002;Schwarcz et al, 1992). The idea was reinforced by the discovery of specific mechanisms controlling KYNA synthesis in the brain (Gramsbergen et al, 1997) and, in particular, by reports of abnormal KYNA levels in nervous tissue and body fluids in a host of neurological and psychiatric disorders (for review see Chen et al, 2009;Nemeth et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Although endogenous KYNA can also activate the G-protein-coupled receptor GPR35 (Cosi et al, 2010;Wang et al, 2006), inhibition of a7nAChRs and, possibly, NMDARs appears to be the primary physiological function of extracellular KYNA in the mammalian brain (see below). As both a7nAChRs and NMDARs are critically involved in many important physiological functions, including cognitive processes (Bannerman et al, 2006;Levin et al, 2006;Robbins and Murphy, 2006;Thomsen et al, 2010), and also have a role in the etiology of neurodegenerative and other catastrophic brain diseases (Kalia et al, 2008;Kantrowitz and Javitt, 2010;Martin and Freedman, 2007;Mudo et al, 2007), detection of KYNA in the mammalian brain (Moroni et al, 1988;Turski et al, 1988) immediately suggested an important role of the metabolite in both physiology and pathology (Pereira et al, 2002;Schwarcz et al, 1992). The idea was reinforced by the discovery of specific mechanisms controlling KYNA synthesis in the brain (Gramsbergen et al, 1997) and, in particular, by reports of abnormal KYNA levels in nervous tissue and body fluids in a host of neurological and psychiatric disorders (for review see Chen et al, 2009;Nemeth et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to characteristic nicotinic agonists, the nAChR can be activated by a novel class of drugs, called allosteric enhancers because they activate these receptors without binding to the acetylcholine-binding site (Akk and Steinbach, 2005;Pereira et al, 2002). The most characteristic examples are physostigmine and galantamine (Reminyl; Janssen Pharmaceutica, Titusville, NJ); both belong to a class of acetylcholinesterase inhibitors approved for symptomatic treatment of schizophrenia and AD.…”
Section: Abbf (Bayer Group) N-[(3r)-1-azabicyclo[222]oct-3-yl]-7-[mentioning
confidence: 99%
“…Endogenous KYNA may therefore affect neuronal excitability and vulnerability by directly or indirectly interfering with both cholinergic and glutamatergic neurotransmission Poeggeler et al, 1998;Cozzi et al, 1999;Wu et al, 2000;Pereira et al, 2002;Schwarcz and Pellicciari, 2002;Sapko et al, 2003). Further, the changes in cerebral KYNA levels observed after prolonged nicotine administration may account for the ability of nicotine to influence neuronal viability in vivo (Akaike et al, 1994;Marin et al, 1994;O'Neill et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, a7 nAChR stimulation normalizes the auditory gating deficit that is observed in rats that have been reared in social isolation (O'Neill et al, 2003). These considerations have stimulated the development of a7 nAChR agonists such as ARR-17779 (Mullen et al, 2000), which interact directly with the binding site for acetylcholine, or of drugs such as galantamine (Reminyl s ), which increase nAChR activity by interacting with a site close to, but distinct from, the acetylcholine-binding site (Pereira et al, 1994(Pereira et al, , 2002Samochocki et al, 2003). It is also noteworthy that one measure of sensory gating abnormalities, diminished inhibition of the P50 evoked response to repeated auditory stimuli, has been linked to the chromosome 15q14 locus of the a7 nAChR gene (Freedman et al, 1997;Riley et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation